Murine scald models characterize the role of neutrophils and neutrophil extracellular traps in severe burns - Elrod, Julia; Lenz, Moritz; Kiwit, Antonia; Armbrust, Lina; Schönfeld, Lavinia; Reinshagen, Konrad; Pagerols Raluy, Laia; Mohr, Christoph; Saygi, Ceren; Alawi, Malik; Rohde, Holger; Herrmann, Martin; et al. (Frontiers in Immunology, 2023)
Introduction Severe burns cause unique pathophysiological alterations especially on the immune system. A murine scald model was optimized as a basis for the understanding of immunological reactions in response to heat induced injury. The understanding of the roles of neutrophil extracellular traps (NETs) and DNases will support the development of new surgical or pharmacological strategies for the therapy of severe burns. Methods We studied C57BL/6 mice (n=30) and employed four scalding protocols with varying exposure times to hot water. An additional scald group with a shorter observational time was generated to reduce mortality and study the very early phase of pathophysiology. At 24h or 72h, blood was drawn and tissue (wound, liver, lung, spleen) was analyzed for the presence of NETs, oxidative stress, apoptosis, bacterial translocation, and extracellular matrix re-organization. In addition, we analyzed the transcriptome from lung and liver tissues. Results Exposure to hot water for 7s led to significant systemic and local effects and caused considerable late mortality. Therefore, we used an observation time of 24h in this groups. To study later phases of burns (72h) an exposure time of 6s is optimal. Both conditions led to significant disorganization of collagen, increased oxidative stress, NET formation (by immunodetection of H3cit, NE, MPO), apoptosis (cC3) and alterations of the levels of DNase1 and DNase1L3. Transcriptome analysis revealed remarkable alterations in genes involved in acute phase signaling, cell cohesion, extracellular matrix organization, and immune response. Conclusion We identified two scald models that allow the analysis of early (24h) or late (72h) severe burn effects, thereby generating reproducible and standardized scald injuries. The study elucidated the important involvement of neutrophil activity and the role of NETs in burns. Extensive transcriptome analysis characterized the acute phase and tissue remodeling pathways involved in the process of healing and may serve as crucial basis for future in-depth studies.